Road trip : a novel - Andrews, Mary Kay, 1954- (Macmillan Audio, 2026)
Maeve and Therese Dunigan are sisters--but the two have been estranged for years. They could not be more opposite: Maeve, a rule-follower and Therese, a rebel. But when their mother's death brings the family back together, the two find that they have inherited a painting--one that could be worth millions and could save each of them from their respective wolves at the door. The only issue is, the painting might be a fake and the only way the can solve the problem is to find the original. This means a road trip--to Ireland, to their family roots, and to a mysterious crime that occurred years ago. With tensions simmering, the two hit the road and find themselves on twisty lanes, in colorful villages, at local pubs, and with handsome men whose gift of the gab is surpassed only by their charm. Can Maeve and Therese find the real painting, remove a family curse, solve a cold case, and actually survive without killing each other? Join Mary Kay Andrews on a road trip that will entertain you for miles.